Leaf and Seed extracts of Bixa orellana L. exert anti-microbial activity against bacterial pathogens - Tamil Selvi A., Dinesh M. G., Satyan R. S., Chandrasekaran B., Rose C. (Journal of Applied Pharmaceutical Science)
Methanol extracts of the leaf & seed of Bixa orellana L. were studied for in vitro antimicrobial activity against MTCC strains of Staphylococcus aureus, Salmonella typhi, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus fecalis, Vibrio cholera, Moraxella catarrhalis, Acinetobacter sp., Brucella sp. along with fungal pathogens Candida albicans, Aspergillus niger and the dermatophytes Trichophyton mentagrophytes & Trichophyton rubrum. Leaf extract of B. orellana at 1000 µg/ml concentration showed significant inhibition against all the tested bacteria and fungus, with highest inhibition zone (18±0.3 mm) against S. typhi, Acinetobacter sp., T. mentagrophytes and T. rubrum. Seed extract of B. orellana was comparitively less efficacious in most of the tested pathogens, except Brucella sp. which was appreciably inhibited (15±0.1 mm). Minimum Inhibitory Concentration (MIC) of leaf extract was determined as 15.62 µg/ml against S. aureus and 31.25 µg/ml for K. pneumoniae, P. aeruginosa, E. fecalis & S. typhi, on average. Among the dermatophytes, 78.2% inhibition was seen in T. mentagrophytes & T. rubrum. Scanning Electron Microscopic (SEM) studies of the treated P. aeruginosa cells revealed disintegration & aggregation of cells after treatment with the leaf extract. Phytochemical analysis of leaf & seed extracts suggested the presence of flavonoids, tannins, saponins, steroids. Alkaloids were detected only in the leaf & anthroquinones, in the seeds.
Keywords: Bixa orellana L., antibacterial, antifungal, SEM & phytochemical analysis